Impact of exotic insect herbivores on native tritrophic interactions: a case study of the African cotton leafworm, Spodoptera littoralis and insects associated with the field mustard Brassica rapa. (January 2015) - Chabaane, Yosra; Laplanche, Diane; Turlings, Ted C. J.; Desurmont, Gaylord A.; Phillips, Ryan
Summary When exotic herbivores invade new environments, they have the potential to interfere with native predator‐prey relationships. This interference can be indirect, via changes induced in native host plants, and may have cascading consequences at the community level. Here, we investigate the impact of the presence of an exotic generalist insect herbivore, the African cotton leafworm Spodoptera littoralis, on the outcome of native tritrophic interactions between the plant Brassica rapa, the herbivore Pieris brassicae and its parasitoid Cotesia glomerata. In olfactometer choice tests, plants damaged by S. littoralis and plants damaged by both S. littoralis and P. brassicae were consistently less attractive to the parasitoid than plants damaged by P. brassicae alone. Chemical analyses revealed that B. rapa volatiles typically induced by S. littoralis dominated the headspace in case of dual herbivore infestation. In behavioural observations in petri dishes, C. glomerata wasps mistakenly attacked S. littoralis larvae significantly more often when P. brassicae was present, and attacks on both herbivores were comparable in terms of time (attack duration) and energy investment (number of eggs injected). Successful parasitism of S. littoralis was never observed, but larvae exposed to C. glomerata for 24 h exhibited reduced survivorship, possibly as a result of failed parasitism attempts. In tents with herbivore‐infested B. rapa plants, the presence of S. littoralis did not have an effect on the parasitism rates of P. brassicae by C. glomerata, regardless of whether the two species were on the same or on different plants. Field experiments in newly invaded environments are necessary to evaluate the realized impact of S. littoralis. Synthesis. Our study illustrates that exotic herbivores can impact native tritrophic interactions associated with Brassica rapa, even if they cannot be used as prey by native natural enemies. The mechanisms behind such effects, in particular chemical interference with foraging cues via changes in herbivore‐induced plant volatiles, have the potential to be quite general, and their long‐term effects on native communities should not be underestimated.